Reconstructing the Epistemology of Pesantren Scholarship Based on Kitab Turats in the Modern Era - Zaini Miftah; Sauqi Futaqi; Muhtadi Ridlwan (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
The development of pesantren (Islamic boarding school) scholarship based on turats texts (classical Islamic texts) faces complex epistemological challenges, particularly regarding the preservation of classical scholarly traditions amidst the demands of modern knowledge and the necessity of contextualization. This situation highlights the need to maintain the authenticity of turats texts as primary sources of knowledge while simultaneously adapting them to advancements in science and technology. This article focuses on efforts to integrate traditional values ​​with contemporary scientific approaches without compromising the distinctive character of pesantren scholarship. The scarcity of in-depth studies regarding the epistemological processes involved in developing turats-based scholarship that is responsive to changing times underscores the importance of this research. The study employs a qualitative approach involving a literature review, utilizing descriptive analysis of primary sources—supported by secondary documents—and content analysis methods. The findings indicate that the development of *pesantren* scholarship requires an integrative approach that combines traditional and modern methods, supported by competent and innovative human resources. Consequently, epistemological strengthening must be pursued through the revitalization of teaching methods and the development of curricula grounded in the values ​​of turats texts while remaining contextually relevant. Future research could focus on formulating learning models and curricula that bridge tradition and innovation, while also evaluating their effectiveness in sustainably enhancing the quality of pesantren scholarship.